Expressed sequences as candidates for a novel tumor suppressor gene at band 13q14 in B-cell chronic lymphocytic leukemia and mantle cell lymphoma - Stilgenbauer, Stephan; Nickolenko, Jeremy; Wilhelm, Jens Cornelius; Wolf, Stephan; Weitz, Sandra; Döhner, Konstanze; Boehm, Thomas; Döhner, Hartmut; Lichter, Peter (Oncogene, 1998)
Deletions affecting the interval between the RB1 gene and marker D13S25 at band 13q14 are the most frequent genetic abnormalities of B-cell chronic lymphocytic leukemia (B-CLL) and indicate the presence of a novel tumor suppressor gene in this region. In the current study, a high resolution physical map of fragments spanning one megabasepair (Mb) of genomic DNA at the critical 13q14 segment was constructed. To define the minimal region of loss within the RB1 and D13S25 interval, we screened 322 B-CLLs for deletions at either of the two loci. Thirty mantle cell lymphomas (MCLs) were included in the analysis because we observed a 13q14 deletion pattern similar to B-CLL in this disease. The incidence of 13q14 deletions was 51% in B-CLL and 70% in MCL, respectively. No frequent loss of the BRCA2 gene at band 13q12 was found. Detailed deletion mapping at band 13q14 with probes from the RB1-D13S25 interval lead to the identification of a critical deletion region 400 kb in size. Within this region two segments were most frequently affected, one at D13S272 120 kb in size and another 240 kb distal of D13S272 80 kb in size. From these two segments expressed sequences were identified as candidates for the putative 13q14 tumor suppressor gene involved in the pathogenesis of B-CLL and MCL.